Motivation in a Foreign Language Teaching and Learning - Thohir, Lalu (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2017)
In learning English as a foreign language, where learners are separated logistically and psychologically from the target culture, motivation plays a critical role and it is one of the main determining factor in a second/foreign language learning achievement. Motivation is defined as some kind of internal drive which pushes someone to do things in order to achieve something and to achieve success, someone needs to be motivated.Motivation is distinguished into different kinds, such as integrative and instrumental, intrinsic and extrinsic, global, situational and task. However, the most widely cited distinction of motivation is between intrinsic and extrinsic motivation.In the field of language learning, motivation is sometimes distinguished from orientation. As an ideal for self-determined behavior, the intrinsic motivation is considered to be more powerful than extrinsic motivationin the success of learning a language, however, most of learning activities which the language learners do are initiated and driven by extrinsic motivation.There are three areas – goalsand goal setting, learning environment, and interesting classes – in which the language teachers could directly influence the language learners’ motivation and their continuing participation in the classroom. Providing positive feedback and enhancing the autonomous learning are among important means to increase the learners’ motivation. In addition, emphasizing two forms of positive extrinsic motivation – identificationand integration, while minimizing two forms of negative extrinsic motivation – external regulation and introjection could boost the intrinsic motivation of the learners.